Determinants of Chronic Respiratory Symptoms among Pharmaceutical Factory Workers - Sahle Asfaw; Fikre Enquselassie; Yifokire Tefera; Muluken Gizaw; Samson Wakuma; Messay Woldemariam (Journal of Tropical Medicine)
Background. Chronic respiratory symptoms including chronic cough, chronic phlegm, wheezing, shortness of breath, and chest pain are manifestations of respiratory problems which are mainly evolved as a result of occupational exposures. This study aims to assess determinants of chronic respiratory symptoms among pharmaceutical factory workers. Methods. A case control study was carried out among 453 pharmaceutical factory workers with 151 cases and 302 controls. Data was collected using pretested and structured questionnaire. The data was analyzed using descriptive statistics and bivariate and multivariate analysis. Result. Previous history of chronic respiratory diseases (AOR = 3.36, 95% CI = 1.85–6.12), family history of chronic respiratory diseases (AOR = 2.55, 95% CI = 1.51–4.32), previous dusty working environment (AOR = 2.26, 95% CI = 1.07–4.78), ever smoking (AOR = 3.66, 95% CI = 1.05–12.72), and service years (AOR = 1.86, 95% CI = 1.16–2.99) showed statistically significant association with chronic respiratory symptoms. Conclusion. Previous history of respiratory diseases, family history of chronic respiratory diseases, previous dusty working environment, smoking, and service years were determinants of chronic respiratory symptoms. Public health endeavors to prevent the burden of chronic respiratory symptoms among pharmaceutical factory workers should target the reduction of adverse workplace exposures and discouragement of smoking.